KEBIJAKAN GHANA MELAKUKAN EKSPLOITASI MINYAK SEPIHAK KEPADA PANTAI GADING DI TELUK GUINEA - M. Fathur Rahman Elka Putra; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Unilateral activity conducted by Ghana has given impact to their relation with Ivory Coast. Ivory Coast as a country which directly border with Ghana has concerns with expanding exploration and exploitation of Ghana’s petroleum industrial in disputed area. Ghana and Ivory Coast have adjacent coast in the Gulf of Guinea. The parties hold their opposing positions over delimitation of maritime boundary which caused a disputed area in the Gulf of Guinea. This research is aimed to explain the foreign policy of Ghana in disputed area.This research theoretically has built by using Behavioralism perspective on International Relations and supported by Foreign Policy theory from Graham T. Allison. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using subnational group as the level of analyze, the focus on this research is explain the causes of Ghana’s foreign policy unilateral exploiting petroleum over Ivory Coast in the Gulf of Guinea. Reseacrher has formulated answer-hypothesis which revealed the fact that petroleum industrial helps boosting Ghana’s revenue is causes Ghana establish their foreign policy exploiting petroleum in the disputed area unilaterally.Keywords: UNCLOS, Petroleum Industrial, TEN Block, National Interest, Foreign Policy, Unilateral Activity